Thaw depth across an experimental burn severity gradient in far northeastern Siberia, 2012-2017 - Heather D. Alexander (Arctic Data Center, 2018)
Fire severity is increasing across the boreal forest biome as climate warms, and initial post-fire impacts on tree demographic processes and soil conditions could be an important determinant of long-term forest structure and carbon dynamics. To examine soil burn severity impacts on permafrost thaw depth, we conducted experimental burns in summer 2012 that created a gradient of residual post-fire soil organic layer (SOL) depth within a mature, sparse-canopy Cajander larch (Larix cajanderi Mayr.) forest in the Eastern Siberian Arctic. Pre-treatment and during the growing season from 2012 to 2017, we measured permafrost thaw depth along the burn severity gradient.